PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP KUALITAS LABA - Desy Budi Lestari, 14.05.52.0144; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2018)
This study examines the effect of good corporate governance, firm size and liquidity on earnings quality, where good corporate governance includes independent commissioners, managerial ownership, institutional ownership, audit committee and board size.The sample in this study used 93 data from 31 manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2016 by using purposive sampling method. The analysis tools used are normality test, classical assumption test, multiple linear regression test, model test and hypothesis test. Based on the research that has been done, the results of this study showed that independent commissioners, board size and liquidity have a significant positive effect on earnings quality. While managerial ownership, institutional ownership, audit committee and firm size have no significant effect on earnings quality. Keywords: Good Corporate Governance, Firm Size, Liquidity and Earnings Quality